2016
DOI: 10.18869/acadpub.jafm.68.236.24289
|View full text |Cite
|
Sign up to set email alerts
|

Combustion of Methane and Biogas Fuels in Gas Turbine Can-type Combustor Model

Abstract: The paper presents the numerical simulation on combustion of methane and biogas mixtures in the swirl burner can-Type of gas turbine combustion chamber. The study deals with the impact of mass fraction of carbon dioxide for biogas on emissions of noxious compounds during combustion. The investigations were done for four different fuels: pure methane (100% CH4), three biogases (90%CH4+10%CO2, 75%CH4+25%CO2 and 70%CH4+30%CO2), with the constant value of equivalence ratio ( = 0.95). The numerical results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
(12 reference statements)
1
1
0
Order By: Relevance
“…Multiple studies (Fischer et al 19 ; Khaleghi et al 20 ) looked into the effect of CO 2 content in biogas on CO formation for non-premixed and premixed combustion in burners and modelled combustors, and the results showed that higher CO 2 content leads to lower flame stability and temperature, and thus higher CO emission. A monotonic NOx reduction with increasing CO 2 level in biogas was previously documented in a similar study (Guessab et al 21 ). By altering the H 2 and CO 2 levels in biogas, the combustion properties can be changed.…”
Section: Introductionsupporting
confidence: 80%
“…Multiple studies (Fischer et al 19 ; Khaleghi et al 20 ) looked into the effect of CO 2 content in biogas on CO formation for non-premixed and premixed combustion in burners and modelled combustors, and the results showed that higher CO 2 content leads to lower flame stability and temperature, and thus higher CO emission. A monotonic NOx reduction with increasing CO 2 level in biogas was previously documented in a similar study (Guessab et al 21 ). By altering the H 2 and CO 2 levels in biogas, the combustion properties can be changed.…”
Section: Introductionsupporting
confidence: 80%
“…The flame propagation speed increased with the increase in the hydrogen ratio. Guessab et al, [3] investigated the combustion of methane and biogas fuels in a model gas turbine burner. In the study where the addition of CO2 at different rates was tested, it was observed that the increase in the CO2 ratio increased the flame stability.…”
Section: Introductionmentioning
confidence: 99%